Financial Performance Analysis Using the Du Pont System Method - Ana Francisca Ribeiro Da Cruz; Agus Sukoco; Rossa Adinda Saputri (NAROTAMA UNIVERSITY, Indonesia, 2022)
This study aims to determine the results of the financial performance of companies in the food sector listed on the Indonesia Stock Exchange (IDX) from 2016 to 2020. study was used to measure financial performance using the results of the Du Pont system analysis: ROE, NPM, TATO, TATE , Capital structure impact, Tax Ratio, PPE/Capital Assets Turn over, WCT, Ebit Margin, GPM, DEP&AMORT, R&D, PTO, ITO, RTO, CTO. This study uses quantitative data and the data used is secondary data with collection techniques using data available on the website. The results of calculations using the du pont system analysis method at PT. Indofood Sukses Makmur Tbk shows good financial performance on indicators, TATE, Tax Ratio, EM, GPM, R&D, PTO, and CTO. Poor financial performance on indicators ,ROE, NPM, TATO, CSI, PPE/CAT, WCT, SG&A, DEP&AMORT, ITO, and RTO. Financial performance of PT. Tiga Pilar Sejahhtera Food Tbk with du pont method analysis showed good performance on indicators, ROE, NPM, TATE, Tax Ratio, EM, R&D and CTO. Poor financial performance on indicators, TATO, CSI, PPE/CAT, WCT, GPM, SG&A, DEP&AMORT, PTO, ITO and RTO.